A comparative study of information literacy provision at university libraries in South Africa and the United Arab Emirates: A literature review. Issue 1 (1st February 2016) - Moyo, Mathew; Mavodza, Judith
Abstract : Purpose: – The purpose of this paper is to establish and compare the provision of information literacy (IL) skills to university students both at undergraduate and graduate levels in South Africa (SA) and the United Arab Emirates (UAE). This could in turn inform the development of appropriate/suitable IL programmes to support teaching and learning. Design/methodology/approach: – A review of available scholarly papers is performed for information collection. Findings: – The findings can identify variations in IL provision within and across disciplines, deficiencies in local current and ongoing research. Research limitations/implications: – It must be noted that this is a review and conclusions from it are expected to reveal areas that require more in-depth study. Practical implications: – The study's contribution to the field of IL lies in its revelation of what is understood by IL provision and how the ACRL standards are used to guide practice in the two different regions of the world. Originality/value: – The study is the first of its kind which compares IL practices at university libraries in SA and the UAE. It will assist policymakers and librarians in the development of appropriate IL programmes in support of teaching and learning.